Baroque fictions : revisioning the classical in Marguerite Yourcenar - Colvin, Margaret Elizabeth (Faux titre, 2005)
This volume is the first in-depth study of the French novelist Marguerite Yourcenar's fiction to contend that the author's texts exhibit in unexpected ways numerous characteristics of the neobaroque. This subversive, postmodern aesthetic privileges extravagant artistic play, flux, and heterogeneity. In demonstrating the affinity of Yourcenar's texts with the neobaroque, the author of this study casts doubt on their presumed transparency and stability, qualities associated with the French neoclassical tradition of the past century, where the Yourcenarian œuvre is most often placed. Yourcenar's.